2020
DOI: 10.3389/fendo.2020.00064
|View full text |Cite
|
Sign up to set email alerts
|

Asprosin: A Novel Player in Metabolic Diseases

Abstract: Asprosin, a novel glucogenic adipokine, is encoded by two exons (exon 65 and exon 66) of the gene Fibrillin 1 (FBN1) and mainly synthesized and released by white adipose tissue during fasting. Asprosin plays a complex role in the central nervous system (CNS), peripheral tissues, and organs. It is involved in appetite, glucose metabolism, insulin resistance (IR), cell apoptosis, etc. In this review, we will summarize the newly discovered roles of asprosin in metabolic diseases including diabetes, obesity, polyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
76
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 34 publications
3
76
1
Order By: Relevance
“…The experiments carry by Duerrschmid et al in mice model observed that asprosin, not only activated AgRP+ neurons, (only ∼50% were asprosin responsive by cells which contain the components necessary for transducing the asprosin-dependent signal) via a G-protein, adenylate cyclase, cAMP, and PKA pathway, but also inhibited ∼85% of the POMC + neurons. 15 The balance resulted in appetite stimulation 16 (Fig. 4 ).…”
Section: Asprosin and Obesity Managementmentioning
confidence: 99%
“…The experiments carry by Duerrschmid et al in mice model observed that asprosin, not only activated AgRP+ neurons, (only ∼50% were asprosin responsive by cells which contain the components necessary for transducing the asprosin-dependent signal) via a G-protein, adenylate cyclase, cAMP, and PKA pathway, but also inhibited ∼85% of the POMC + neurons. 15 The balance resulted in appetite stimulation 16 (Fig. 4 ).…”
Section: Asprosin and Obesity Managementmentioning
confidence: 99%
“…2 Recent study has pointed out that asprosin plays a crucial role in lipid metabolism and glucose homeostasis. 1,3,4 Exemplary, several clinical studies reported increased asprosin levels in patients with obesity, type 1 diabetes mellitus (T1DM) and type 2 diabetes mellitus (T2DM). [5][6][7] As a novel adipokine, asprosin has demonstrated a positive correlation with adiponectin, and a negative correlation with leptin.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, the expression and secretion of asprosin are affected by the nutritional or metabolic state of the body, and it can regulate the metabolism of glucose and lipid in different degrees. 1,3,4 Latest report indicated that anti-asprosin can reduce serum glucose, blood urea nitrogen, serum creatinine, and proteinuria, and increase creatinine clearance rate in a dose-dependent manner. More importantly, it can delay the pathophysiological and biochemical progress of kidney in high fat diet/streptozotocin (STZ)-induced type 2 diabetic rat models.…”
Section: Introductionmentioning
confidence: 99%
“…The latest research performed by Liu et al [ 7 ] have revealed that asprosin binds to the central OLFR734 receptor and promotes appetite by enhancing olfaction and activating AgRP neuron. Moreover, many clinical studies have observed that serum asprosin levels are increased in patients with metabolic diseases such as obesity, type 2 diabetes, and polycystic ovary syndrome (PCOS) [ 8 11 ]. Therefore, asprosin may be a potential biomarker for abnormal glucolipid metabolism related diseases [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many clinical studies have observed that serum asprosin levels are increased in patients with metabolic diseases such as obesity, type 2 diabetes, and polycystic ovary syndrome (PCOS) [ 8 11 ]. Therefore, asprosin may be a potential biomarker for abnormal glucolipid metabolism related diseases [ 11 ].…”
Section: Introductionmentioning
confidence: 99%